10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
UNLABELLED: Müller, Julian, Anna Titz, Pascal Yoncaova, Michael Furian, Mona Lichtblau, Ruth McQuillan, Marshall Dozier, Evropi Theodoratou, and Silvia Ulrich.The association between chronic high-altitude exposure and increased pulmonary vascular resistance in healthy high-altitude residents. A systematic review and meta-analysis. High Alt Med Biol. 00:00-00, 2026. BACKGROUND: At high altitude, hypoxia triggers pulmonary vasoconstriction and vascular remodeling, potentially elevating pulmonary vascular resistance (PVR). Whether chronic high-altitude exposure raises PVR to clinically meaningful levels remain unclear, particularly in the context of long-term physiological adaptation. OBJECTIVES: To synthesize and assess the evidence of the association between chronic high-altitude exposure and PVR in healthy high-altitude residents. ELIGIBILITY CRITERIA: Peer-reviewed studies reporting PVR measured by echocardiography or right heart catheterization in healthy adults permanently residing at high altitude were eligible. Studies involving acute or intermittent hypoxia exposure, animal subjects, or pediatric populations were excluded. METHODS: A systematic literature search was conducted across four electronic databases (Medline, Embase, Scopus, and Web of Science) covering all records from database inception through October 2025. Two reviewers independently screened abstracts and full texts using Covidence software. Risk of bias was assessed using the modified National Heart, Lung, and Blood Institute Quality Assessment Tool. Random-effects meta-analyses were performed. A sensitivity analysis excluded studies with high risk of bias. RESULTS: Out of 464 identified records, 13 studies met eligibility criteria, comprising 854 participants (80% males) across different populations in South America, Asia, and Africa. Most studies were conducted between 3,500 and 4,000 m. The primary pooled PVR estimate was 2.4 WU (2.0-2.8 WU), which slightly exceeds the sea level upper limit of normal (2.0-2.2 WU). Following exclusion of high-risk-of-bias studies, the estimate decreased to 2.2 WU (1.9-2.5 WU), approaching the upper limit of normal. However, substantial heterogeneity was observed in all analyses. LIMITATIONS: The small number of included studies, heterogeneity, measurement technique, predominance of male participants, and narrow altitudinal range of most studies limit the generalizability of the findings. CONCLUSIONS: Chronic high-altitude exposure is associated with a slight elevation in PVR in otherwise healthy individuals. However, the clinical significance of this elevation remains unknown. These findings highlight the need for altitude-specific reference values, prospective studies, and further investigation into the role of blood viscosity in interpreting PVR at high altitude.